Value of the portal venous phase in evaluation of treated hepatocellular carcinoma following transcatheter arterial chemoembolisation. Issue 11 (November 2017) - Lam, A.; Fernando, D.; Sirlin, C.C.; Nayyar, M.; Goodwin, S.C.; Imagawa, D.K.; Lall, C.
Abstract : Aim: To evaluate the utility of the portal venous phase on multiphasic computed tomography (CT) after treatment of hepatocellular carcinoma (HCC) with trans-arterial chemoembolisation (TACE). Materials and methods: This was a retrospective review of patients who underwent TACE for HCC between 1 April 2012 and 21 December 2014, with appropriate multiphasic, pre- and post-procedural CT examinations. The maximum non-contrast, arterial phase, and portal venous phase attenuation values of the tumour and tumour bed were evaluated within a region of interest (ROI), with values adjusted against background hepatic parenchyma. Linear regression analyses were performed for both the arterial and venous phases, to assess the level of enhancement and to determine if the venous phase had additional value in this setting. Results: A total of 86 cases from 51 patients were reviewed. All pre-procedural CT examinations of lesions demonstrated arterial phase enhancement with portal venous and delayed phase washout compatible with HCC. The post-procedural CT examinations following TACE revealed expected decreased arterial enhancement. Sixty-five cases (76%) showed persistent non-enhancement on the portal venous phase following embolisation therapy. A total of 21 cases (24%), however, demonstrated progressive portal venous hyper enhancement. Linear regression analysis demonstrated a statistical significance between the difference in maximal arterial and portal venous enhancement in these cases. Conclusion: Following TACE, the treated lesion may demonstrate portal venous phase hyper-enhancement within the tumour bed. As such, full attention should be given to these images for comprehensive evaluation of tumour response following treatment. Highlights: Changes in the micro-hemodynamic properties of hepatocellular carcinoma permit diagnosis via multiphasic CT and MR imaging. Embolic agents delivered during intra-arterial, liver-directed therapies disrupt the arteries supplying the tumour. Interval development of portal venous enhancement can be seen in a subset of patients following treatment. The exact cause is unclear, however it is likely multifocal in nature and related to changes in the microvascular environment. Further studies are necessary to further elucidate the aetiology and its clinical implications.